Proteomics, dietary intake, and changes in cardiometabolic health within a behavioral weight‐loss intervention: A pilot study. Issue 11 (2nd November 2022) - Hill, Emily B.; Siebert, Janet C.; Yazza, Deaunabah N.; Ostendorf, Danielle M.; Bing, Kristen; Wayland, Liza; Scorsone, Jared J.; Bessesen, Daniel H.; MacLean, Paul S.; Melanson, Edward L.; Catenacci, Victoria A.; Borengasser, Sarah J.
Abstract: Objective: Identifying associations among circulating proteins, dietary intakes, and clinically relevant indicators of cardiometabolic health during weight loss may elucidate biologically relevant pathways affected by diet, allowing for an incorporation of precision nutrition approaches when designing future interventions. This study hypothesized that plasma proteins would be associated with diet and cardiometabolic health indicators within a behavioral weight‐loss intervention. Methods: This secondary data analysis included participants ( n = 20, mean [SD], age: 40.1 [9.5] years, BMI: 34.2 [4.0] kg/m 2 ) who completed a 1‐year behavioral weight‐loss intervention. Cardiovascular disease‐related plasma proteins, diet, and cardiometabolic health indicators were evaluated at baseline and 3 months. Associations were determined via linear regression and integrated networks created using Visualization Of LineAr Regression Elements (VOLARE). Results: A total of 16 plasma proteins were associated with ≥1 diet or health indicator at baseline ( p < 0.001); changes in 42 proteins were associated with changes in diet or health indicators from baseline to 3 months ( p < 0.005). Baseline tumor necrosis factor receptor superfamily member 10C (TNFRSF10C) was associated with intakes of dark green vegetables ( r = −0.712), and fatty acid‐binding protein 4 (FABP4) was associated with intakes of unsweetened coffee ( r = −0.689). Changes in refined‐grain intakes were associated with changes in scavenger receptor cysteine‐rich type 1 protein M130 (CD163; r = 0.725), interleukin‐1 receptor type 1 (IL1R‐T1; r = 0.624), insulin ( r = 0.656), and triglycerides ( r = 0.648). Conclusions: Circulating cardiovascular disease‐related proteins were associated with diet and cardiometabolic health indicators prior to and in response to weight loss. Abstract :